Characterization of the Influenza Virus Inhibiting Fractions of Bergenia ligulata - Rajbhandari, M; Schoepke, Th (Nepal Journal of Science and Technology, 2012)
In the course of screening of plant extracts for anti-influenza viral activity, 50% aqueous methanolic extract exhibited antiviral activity against influenza virus A. Bio-assay guided fractionation of the extract led to the indication of the presence of condensed tannins as the active constituents. This was confirmed by chemical tests as well as by thin layer chromatographic comparison with known tannin containing plant extracts. The active fractions were also analysed for the presence of carbohydrates by gas chromatography. DOI: http://dx.doi.org/10.3126/njst.v12i0.6515 Nepal Journal of Science and Technology 12 (2011) 290-295